Correction to: Development and content validity of the Abilitator: a self-report questionnaire on work ability and functioning aimed at the population in a weak labour market position - Miia Wikström; Heidi Anttila; Minna Savinainen; Anne Kouvonen; Matti Joensuu (BMC, 2020)
It was highlighted that the original article [1] contained an ambiguity in the citation of Reference 2 in the Results section.